Науково-дослідний інститут історичної урбаністики - Константінова, В.; Лиман, І. (Місто: історія, культура, суспільство, 2016)
Повідомлення присвячене основним напрямкам діяльності створеного у 2012 р. Науково-дослідного інституту історичної урбаністики, якими є багатоаспектне наукове дослідження міської історії; розбудова сайту НДІ; робота в складі редколегії та авторів історико-культурологічного альманаху “Фронтири міста”; проведення усноісторичних досліджень з міської історії із формуванням архіву усноісторичних інтерв’ю; формування депозитарію кінодокументів з міської історії; створення та забезпечення функціонування в структурі НДІ музею історії БДПУ; громадська діяльність, спрямована на популяризацію історії міст і на взаємодію науковців із суспільством. Сообщение посвящено основным направлениям деятельности созданного в 2012 году Научно-исследовательского института исторической урбанистики, каковыми являются многоаспектное научное исследование городской истории; развитие сайта НИИ; работа в составе редколлегии и авторов историко-культурологического альманаха “Фронтиры города”; проведение устноисторических исследований по городской истории с формированием архива устноисторических интервью; формирование депозитария кинодокументов по городской истории; создание и обеспечение функционирования в структуре НИИ музея истории БГПУ; общественная деятельность, направленная на популяризацию истории городов и на взаимодействие ученых с обществом. The review is dedicated to activities of Research Institute of Urban History. The main attention turns to directions of the work of the Research Institute: 1. Multifaceted studying of urban history (continuation of individual Institute’s members studies on various components of the urban past; realization of joint research projects connected with urbanization; organization of conferences and meetings dedicated to urban issues; cooperation with other research institutions and associations involved in studying urban past); 2. Developing a web-site of the Institute, which should become a platform for communication scholars and the public involved and interested in urban history as well as for publishing articles and archival collections of the Research Institute; 3. Work as an editorial board and authors of historical-cultural anthology “Frontiers of city”. 4. Conducting oral historical research on urban history with the formation of an archive of oral historical narrative (theoretical and practical training for interviewers; preparing and conducting expeditions; systematization, processing the collected materials; preparation of materials for publication); 5. Development and maintenance of the archive of film documents related to urban history (heuristic work in archives; identifying and copying film documents from private collections; participation in creation on the basis of these film documents documentaries and popular science films on the history of cities); 6. Development and maintenance of the depositary of photographs related to the history of “urban space”; 7. Creating in the structure of the Research Institute the Museum of Berdyansk State Pedagogical University, which in a broader context may be considered as a museum of the history of education in an urban area; 8. Public activities aimed at popularization of urban history and at interaction of researchers with society (organization of exhibitions, competitions, etc.; initiation and implementation of public projects).